Opportunity and Challenge for Empowering Indonesian Former Female Migrant Workers Living in Coastal Area - Tandos, Rosita; El Zieni, Asmaa (Prosperity: Journal of Society and Empowerment, 2024)
Studies of transnational domestic workers have been conducted in varied disciplines with different focuses of discussion such as women’s studies, international development, human rights, and social welfare. To figure out the life of female migrant workers living in coastal areas is crucial since the women and community examine some more issues. This study specifically explored the main questions of how is the life of women in the coastal community of Prapag Lor village, the district of Brebes in Central Java Province of Indonesia; how are life’s episodes (before, during, and after working) of the women that worked previously as female migrant domestic workers (FMDWs), and the proposed solutions to improve their lives as FMDWs. To explore all of the points, this study collected data by conducting observation, secondary data analysis, and focus group discussions (FGDs) involving 50 female participants (n=50) aiming to explore the dynamic life of women and people living in coastal areas, life as migrant workers, and efforts to improve the living condition of the women, family and the whole community members.